Nipple and areola diameter in Turkish pubertal girls - Aygun, AD; Akarsu, S; Guvenc, H; Kocabay, K (Elsevier Science Inc, 1998)
The nipple and areola diameter of 498 girls aged 8-17 years were studied with the aim of finding measurable criteria for sexual maturation, including breast and pubic hair development during female puberty. All measurements were made holding a transparent ruler on both sides by the same observer. The smaller of the two measurements was used in the analysis. Significantly nipple and areola development occurred between breast stages BI (2.56 and 14.35 mm), B2 (3.32 and 20.26 mm), B3 (5.21 and 28.84 mm), and B4 (6.28 and 32.03 mm). The nipple and areola diameter were also significantly greater in pubic hair stage (PH)3 (5.05 and 25.24 mm) with respect to PH2 and PH1 (3.46, 2.62 mm and 19.32 15.37 mm, respectively), in PH5 (6.79 and 35.62 mm) with respect to PH4 (6.55 and 32.56 mm). A significant increase in nipple and areola diameter occurs between premenarchal girls and girls-older than 0-2 years postmenarche. Sexual maturation staging by nipple size and by areola size appears to be feasible for female adolescent However, staging by nipple size does not appear to be feasible for B4 and B5 stage, because the incremental gradations are small. (C) Society for Adolescent Medicine, 1998.
31st Conference of the Turku-Pediatri-Kurumu -- OCT 23-27, 1995 -- ISTANBUL, TURKEY
Keywords: nipple size; areola size; puberty; Eastern Turkish girls